IDENTIFICATION IDENTIFICATION OF MORPHOLOGICAL CHARACTERISTICS OF SORGHUM (Sorghum bicolor L.) IN LOWLAND AREAS - Yuliana Hetibestari zega; Irwan Agusnu Putra; Nina Uzila Angkat (Agroprimatech, 2026)
This study aimed to identify the morphological characteristics of six sorghum (Sorghum bicolor L.) varieties cultivated in lowland area, specifically in Lubuk Pakan, Punden Rejo Subdistrict, Deli Serdang Regency, North Sumatra. The research was conducted from July to October 2024 using a Non-Factorial Randomized Block Design (RBD) with one treatment factor (variety) and four replications, resulting in 24 experimental plots. Observed morphological parameters included plant height, stem diameter, internode length, leaf length and width, number of leaves, and leaf midrib color. The results of the study showed that Super 2 variety is a variety with maximum plant height, longest internodes, and widest leaves but is at risk of lodging. Soper 9 variety is a sorghum plant variety that shows the best morphology in the lowlands because it has a thick stem, short internodes and a plant height that is not too high so it has the potential to be resistant to lodging. Suri 4 variety has the longest leaves and the largest number of leaves tends to have a greater photosynthetic capacity. All accessions that have been characterized do not have diversity in the color of the midrib of the leaf, namely white.